What Does the Examination for Professional Practice in Psychology Step 2 (EPPP Step 2) Mean for College Counseling: The ASPPB Perspective. Issue 1 (2nd January 2017) - Rodolfa, Emil; Webb, Carol; Horn, Jacqueline
ABSTRACT: We appreciate the opportunity to respond to the Editorial in this issue of the Journal of College Student Psychotherapy by editors Philip Rosenbaum and Ryan Weatherford, who express concerns about the new Examination for Professional Practice in Psychology Step 2 (EPPP Step 2). Our discussion describes the constellation of factors that influenced ASPPB's decision to develop the EPPP Step 2 at this point in time. We also respond to the concerns expressed about the increasing costs of graduate training and the timing of the EPPP Step 2. Finally this commentary will highlight the difference between the training and licensing processes and will describe how the EPPP Step 2 will help licensing boards fulfill their mandate to protect a vulnerable public.